2020
DOI: 10.26504/rs114
|View full text |Cite
|
Sign up to set email alerts
|

How does Irish Healthcare Expenditure compare internationally?

Abstract: The mission of the Economic and Social Research Institute is to advance evidencebased policymaking that supports economic sustainability and social progress in Ireland. ESRI researchers apply the highest standards of academic excellence to challenges facing policymakers, focusing on 12 areas of critical importance to 21st century Ireland. The Institute was founded in 1960 by a group of senior civil servants led by Dr T.K. Whitaker, who identified the need for independent and in-depth research analysis to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…It includes services provided in the community such as general practice, public health nursing (PHN), community-based therapies, and long-term care (Smith et al, 2019). Services provided in long-term care are often characterised as social care (Wren and Fitzpatrick, 2020).…”
Section: Overview Of the Non-acute Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…It includes services provided in the community such as general practice, public health nursing (PHN), community-based therapies, and long-term care (Smith et al, 2019). Services provided in long-term care are often characterised as social care (Wren and Fitzpatrick, 2020).…”
Section: Overview Of the Non-acute Systemmentioning
confidence: 99%
“…Projected demand for these services was included in a preceding report (Wren et al, 2017), and has been shown to account for a significant amount of care in Ireland. In addition, delivery of these services involves a sizeable proportion of the frontline health and social care workforce in Ireland (Smith et al, 2019), as well as accounting for a high proportion of the total health and social care budget (Wren and Fitzpatrick, 2020).…”
Section: Non-acute Services Included In Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide context in which to frame a discussion of the healthcare system data infrastructure in Ireland, we provide a brief overview of the healthcare system itself. A number of recent ESRI publications discuss some of the specific parts of the system in greater detail (Keane et al, 2021;Nolan et al, 2014;Smith et al, 2019;Walsh et al, 2019a;Walsh et al, 2019b;Wren and Fitzpatrick, 2020;.…”
Section: Healthcare Systemmentioning
confidence: 99%